The impact of internship experience on professional identity, motivation, and attitude among aviation service majors: a cross-sectional empirical study - Wang, Fangming (Frontiers in Psychology, 2025)
IntroductionChina’s rapidly expanding aviation industry has created an urgent need for a motivated and professionally committed workforce. This study examined whether internship experience influences aviation students’ career motivation and professional attitude through the mediating role of professional identity.MethodsA cross-sectional survey was conducted with 414 aviation service students using validated psychological measures. Mediation analysis was performed using PROCESS Model 4 with 5,000 bootstrap samples. Gender and first-choice major were included as covariates.ResultsHigher-quality internship experiences significantly enhanced students’ professional identity, which strongly predicted both career motivation (β = 0.50***) and professional attitude (β = 0.48***). Professional identity partially mediated the effect of internship experience on career motivation (indirect effect = 0.30) and fully mediated its effect on professional attitude (indirect effect = 0.24**).DiscussionThese findings demonstrate that internships shape students’ long-term career outcomes primarily by strengthening their professional identity rather than through direct experiential effects alone. Professional identity is therefore a critical psychological mechanism in aviation talent development, emphasizing the need for identity-supportive internship programs.